延續或斷裂？從能力到素養的課程改革意涵 Continuity or Rupture? The Implication of the Debate of Skills/Capabilities and Competencies for Curriculum Reform - 林永豐 Yung-Feng Lin (Higher Education Foundation, 2018)
在《十二年國民基本教育課程綱要總綱》的諸多變革之中，能力與素養的區別是各界關心的重要議題之一。新課綱之中，既有九年一貫課程綱要中所使用的概念，如「十大基本能力」與「分段能力指標」等詞均未再沿用，出現「核心素養」與「學習重點」等概念，而此一改變引發了諸多疑慮。本研究試圖從新、舊課綱的政策發展脈絡，參照核心素養論述理念，探究能力與素養兩個概念，以釐清兩者在概念與內涵的差異；繼之探討兩者在教育目標分類中的角色，以理解新課綱中有關核心素養的進步內涵。本研究主張，九年一貫課程綱要到十二年國民基本教育課程綱要不是一個斷裂式的跳躍，而是一個延續性的發展。根據本研究的分析，九年一貫課程綱要中能力概念的主要內涵，在新課綱的核心素養與學習重點中都得到延續。儘管如此，新課綱強調素養導向仍具意義。首先，從對中文與英文中能力與素養概念的分析可得知，「素養」強調廣義的能力概念，包括功能性知能與共通性知能兩個重要內涵。其次，三面九項核心素養承續聯合國教科文組織、經濟合作暨發展組織、歐盟等國際組織的核心素養論述，凸顯面對未來多樣而複雜的社會變遷，有必要培養年輕人具備各種跨領域的共通性能力，因此，更得以彰顯新課綱的未來導向。 The newly introduced curriculum guideline for the 12 year basic education by the Ministry of Education has brought many concerns as well as interests. One of these concern is about the clarifi cation and difference between skills, capability and competency. The concepts of key competencies and competence-indicators are both re-conceptualized in the new curriculum guideline. The main purpose of this paper was to investigate different views about these key terminologies and their underlying rationales. Relative issues around the debate of key competency w ere discussed. This paper argued that the curriculum reform from the current to the coming curriculum guideline is continuous rather than a sudden break. The main ideas underlying the concept of competence in the previous 1-9 year curriculum guideline is largely maintained in the new 1-12 year basic education curriculum. Also, the idea of competencies and key competencies are kept to addressed cognitive, effective and psychomotor objectives. In addition, in the new curriculum guideline, both functional literacy and transversal competencies are included. Furthermore, the progressive approach of the curriculum reform is highlighted.